Controlling long-chain branching in EPDM via post-reactor modification
By performing electron beam radiation treatment on ethylene/propylene/nonconjugated polyene terpolymers, the problem of difficult control of LCB levels in metallocene catalytic EPDM in the prior art is solved, and the high LCB characteristics of terpolymers are achieved. Improves its rheological and physical properties.
Patent Information
- Application Number
- CN202080050941.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-26
- Filing Date
- 2020-06-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-06-18
AI Technical Summary
The prior art is difficult to effectively increase the level of long-chain branching (LCB) in metallocene-catalyzed ethylene-propylene-diene monomer terpolymers (EPDMs).
Branched terpolymers with Mooney viscosity between 25 MU and 135 MU were formed by exposing the pure ethylene/propylene/nonconjugated polyene terpolymer to electron beam radiation of 0.2 MRad to 1.3 MRad.
The Mooney viscosity and rheological ratio of the terpolymer are significantly increased, improving its physical and rheological properties, and enhancing its elastic and shear thinning characteristics.
Smart Images

Figure BDA0003468094050000061 
Figure BDA0003468094050000062 
Figure BDA0003468094050000191
Abstract
Description
Background Art
[0001] Ethylene-propylene-diene monomer terpolymers (EPDM) having a molecular architecture including long chain branching (LCB) are known. LCB introduces side chains into the main chain of EPDM, significantly changing the rheological and physical properties of EPDM, for example, the elasticity and shear thinning characteristics of EPDM increase with increasing LCB. Compared with non-branched EPDM, the benefits of high LCB EPDM include reduced cold flow, higher green strength, higher resistance to collapse during hollow part extrusion, better foamability, faster extrusion rate, faster mixing, lower mixer energy consumption, higher filler loading and reduced melt fracture.
[0002] The selection of catalysts used in the polymerization and the polymerization process conditions provide a means of adjusting the level of LCBs in the EPDM framework. Ziegler Natta (ZN) catalysts (e.g., titanium-based catalysts or vanadium-based catalysts) can introduce LCBs into EPDM during the polymerization process. However, the extent of LCBs is difficult to control, for example, the ZN polymerization process tends to form undesirable cross-linked EPDMs that lead to gel formation. The ZN polymerization process also produces EPDMs with a broad composition distribution and a broad molecular weight distribution.
[0003] Metallocene catalysts (e.g., zirconium-based catalysts) produce EPDM in a solution polymerization process. Metallocene catalysts generally produce EPDM with a more uniform composition distribution, narrower MWD, and a more linear molecular architecture than ZN-catalyzed EPDM. However, metallocene catalysts generally produce lower levels of LCB than ZN-catalyzed EPDM.
[0004] Thus, the art recognizes the need for a high LCB EPDM. The art further recognizes the need for a method of increasing the LCB in a metallocene-catalyzed EPDM. Summary of the invention
[0005] A method is disclosed herein. In one embodiment, the method includes providing a pure ethylene / propylene / non-conjugated polyene terpolymer (n-terpolymer) having a Mooney viscosity (ML (1+4) at 125°C) of less than 100 Mooney units (MU). The method includes exposing the n-terpolymer to electron beam radiation at a dose of 0.2 megarads (MRad) to 1.3 MRad. The method includes forming a branched ethylene / propylene / non-conjugated polyene terpolymer (b-terpolymer) having a Mooney viscosity (ML (1+4) at 125°C) of 25 MU to 135 MU.
[0006] Compositions are also disclosed herein. In one embodiment, the composition includes a branched ethylene / propylene / non-conjugated polyene terpolymer (b-terpolymer) comprising: (A) a Mooney viscosity (ML 1+4 at 125°C) of 35MU to 120MU; (B) a rheological ratio of 55 to 110; and (C) a phase angle δ of 20° to 39°.
[0007] definition
[0008] All references herein to the Periodic Table of the Elements shall refer to the Periodic Table published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more Groups shall be to the Group or Groups reflected in such Periodic Table using the IUPAC system for numbering the Groups.
[0009] For purposes of U.S. patent practice, the contents of any cited patent, patent application, or publication are incorporated by reference in their entirety (or their equivalent U.S. versions are incorporated by reference), particularly with respect to disclosure of definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure) and common knowledge in the art.
[0010] The numerical ranges disclosed herein include all values from the lower limit to the upper limit and include the lower limit and the upper limit. For the range containing explicit values (e.g., 1 or 2 or 3 to 5 or 6 or 7), any sub-ranges (e.g., 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.) between any two explicit values are included.
[0011] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0012] As used herein, the term "composition" refers to a mixture of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0013] The terms "comprises," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed by using the term "comprising" may include any additional additives, adjuvants, or compounds (whether polymeric or otherwise), unless otherwise indicated. In contrast, the term "consisting essentially of excludes any other components, steps, or procedures from the scope of any subsequent narration, except those that are not essential for operability. The term "consisting of" excludes any components, steps, or procedures that are not specifically depicted or listed. Unless otherwise stated, the term "or" refers to the listed members individually and in any combination. The use of the singular includes the use of the plural, and vice versa.
[0014] "Ethylene-based polymers" are polymers containing more than 50% by weight of polymerized ethylene monomers (by the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene-based polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene-based polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene-based polymers (polyethylene) include low-density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low-density polyethylene (LLDPE), ultra-low-density polyethylene (ULDPE), very low-density polyethylene (VLDPE), multi-component ethylene-based copolymers (EPE), ethylene / alpha-olefin multi-block copolymers (also referred to as olefin block copolymers (OBC)), single-site catalyzed linear low-density polyethylene (m-LLDPE), substantially linear or linear plastomers / elastomers and high-density polyethylene (HDPE). In general, polyethylene can be produced using heterogeneous catalyst systems (such as Ziegler-Natta catalysts), homogeneous catalyst systems comprising Group 4 transition metals and ligand structures (e.g., metallocenes, non-metallocene metal centers, heteroaryls, isovalent aryloxyethers, phosphinimines, etc.) in gas phase fluidized bed reactors, liquid phase slurry reactors, or liquid phase solution reactors. Combinations of heterogeneous and / or homogeneous catalysts can also be used in single reactor or dual reactor configurations. In one embodiment, the ethylene-based polymer does not contain aromatic comonomers polymerized therein.
[0015] The terms "interpolymer" and "copolymer" refer to polymers prepared by polymerizing at least two different types of monomers. These general terms include classical copolymers, i.e., polymers prepared from two different types of monomers; and polymers prepared from more than two different types of monomers, such as terpolymers, tetrapolymers, etc.
[0016] As used herein, the term "electron beam radiation" or ("electron beam") includes the generation of an electron beam from a heated cathode filament (usually tungsten). The electrons emitted from the cathode are accelerated in an electric field applied between the cathode and the anode. The energy gain of the electron beam is proportional to the accelerating voltage. The energy is measured in eV (electron volts), and accelerators up to 10 MeV are commercially available. The dose of the electron beam is measured in megarads (MRad). When the electron beam enters the polymer, it ionizes and excites the molecules, resulting in the displacement of hydrogen atoms and the formation of free radicals. The combination of two free radicals forms a branch. The type of branching formed by this method is H-type or tetrafunctional.
[0017] As used herein, the term "entanglement molecular weight" is described as follows. A plot of the logarithm of the structural undeformed mechanical properties of a polymer melt versus the logarithm of the molecular weight shows an initial weak linear correlation, followed by a transition at about 10 kDa showing a strong dependence on the molecular weight. The "transition molecular weight" is referred to as the "entanglement molecular weight". Polymers above the entanglement molecular weight are suitable for use as plastics, while those below the entanglement molecular weight exhibit characteristics of low molecular weight materials (usually brittle powders). For example, candle wax is a low molecular weight polyolefin with the same molecular structure as polyethylene.
[0018] As used herein, the term "long chain branching" or ("LCB") refers to the presence of side chains on the ethylene / propylene / diene monomer terpolymer, wherein the side chain molecular weight is greater than the entanglement molecular weight of the polymer.
[0019] The term "polymer" refers to a compound prepared by reacting (i.e., polymerizing) a set of monomers, wherein the set of monomers is either a homogeneous (i.e., only one type) set of monomers or a heterogeneous (i.e., more than one type) set of monomers. The term polymer as used herein includes the term "homopolymer," which refers to a polymer prepared from a homogeneous set of monomers, and the term "interpolymer" as defined below.
[0020] The term "terpolymer" refers to a polymer prepared by polymerizing three different types of monomers.
[0021] Test Method
[0022] Mooney Viscosity Test: The EPDM rubber Mooney viscosity is measured in a Mooney shear disc viscometer according to ASTM 1646-04. The instrument is an Alpha Technologies Mooney Viscometer 2000. The torque of the rotor rotating at 2 rpm is measured by a torque transducer. After the platen is closed, the sample is preheated for 1 minute (min). The motor is then started and the torque is recorded over a period of 4 minutes. The results are reported in Mooney units (MU) as "ML (1+4) at 125°C". The term "ML" means that a large rotor "Mooney Large" is used in the viscosity test, where the large rotor is a standard size rotor. The Mooney viscosity (MV) measures the flow resistance of a polymer at relatively low shear rates and indicates the fluidity of the polymer.
[0023] Mooney relaxation area (MLRA) data is obtained from Mooney viscosity measurement, wherein the test sample relaxes after the rotor stops. At the end of the Mooney viscosity test, the rotation of the disc stops within 0.1 seconds (s). The collection of relaxation data usually starts 1 second after the rotor stops, and lasts for at least 2 minutes (min) after the rotor stops. The reported MLRA value is the integral area (MLRA (1'+4'+2')) under the Mooney torque-relaxation time curve from 1 second to 120 seconds. The MLRA value indicates the elasticity of the polymer and can be regarded as an energy storage term. Higher MRLA values indicate that after removing the applied strain, the test sample stores more energy and requires more time to relax (i.e., dissipate the stored energy). Compared with less elastic polymers (e.g., those with less long-chain branched structures), polymers with greater elasticity (e.g., those with more long-chain branched structures) generally show higher MLRA values. MLRA is reported in Mooney units-seconds (MU s).
[0024] As used herein, the term "MLRA / ML ratio" is the ratio of the Mooney relaxation area to the Mooney viscosity and is an abbreviated form of "MLRA / ML (1+4) at 125°C". The MLRA / ML ratio indicates the degree of melt elasticity of the polymer and is proportional to the degree of melt elasticity. The MLRA / ML ratio is reported in seconds (s).
[0025] Rubber Rheological Analysis (RPA): Rubber rheological analysis was performed according to ASTM D6204 using a rotorless oscillatory shear rheometer, i.e., a Rubber Processing Analyzer (RPA). RPA frequency sweep tests were performed using an Alpha Technologies RPA 2000. Test specimens were cut using a Cutter 2000R. The sample size was between 5 and 7 grams. The test specimen was considered to be of the appropriate size (116% to 160% of the test cavity volume) when the mold was closed when a small piece of the rubber compound was extruded uniformly around the perimeter of the mold. The sample was placed between two sheets of polyester film. For the pure terpolymer, the frequency sweep was performed at 125°C using 5% strain. For the terpolymer composition, the frequency sweep was performed at 100°C using 5% strain. The frequency range was from 0.1 radian / second (rad / s) to 100 rad / s. The stress response is analyzed with respect to amplitude and phase, from which the storage modulus (G′), loss shear modulus (G″), complex viscosity (V), tan δ (i.e., phase angle δ), and complex shear modulus G* are calculated. Modulus values are reported in kilopascals (kPa), phase angles are reported in degrees, and viscosities are reported in Pascal-seconds (Pa·s).
[0026] As used herein, the term "phase angle δ" is the phase lag exhibited between an applied stress and the resultant strain imparted by the stress. For a given dynamic mechanical study, the phase angle δ is measured at a complex shear modulus G* value of 100 kPa and 125°C. When comparing the phase angle δ of a group of polymers, a reduced phase angle δ value generally indicates that the polymer is more elastic.
[0027] The term "rheological ratio" (or "RR") is calculated as the ratio of the complex viscosity at 0.1 rad / s and 125°C to the complex viscosity at 100 rad / s and 125°C; RR equals V0.1 / V100 at 125°C.
[0028] High Temperature Gel Permeation Chromatography Test (“HT GPC Test”): The HT GPC test was performed with a POLYMERCHAR (Valencia, Spain) HT GPC system consisting of an infrared concentration / composition detector (IR-5 detector), a PDI 2040 laser light scattering detector (Agilent) and four capillary bridge viscometers (Malvern) and allowed the determination of the number average molecular weight (M N ), weight average molecular weight (M W ) and Z-average molecular weight (M Z ).
[0029] The columns were four mixed A LS 20 micron columns (Agilent). The detector compartment was operated at 160° C. and the column compartment was operated at 150° C. The carrier solvent was 1,2,4-trichlorobenzene (TCB) containing approximately 250 ppm butylated hydroxytoluene (BHT) and sparged with nitrogen.
[0030] The HT GPC system was calibrated with 21 narrow molecular weight distribution polystyrene standards. The molecular weights of the standards ranged from 580 to 8,400,000 and were arranged in six "cocktail" mixtures, with individual molecular weights separated by at least a factor of ten. The molecular weight data (M ps ) is converted into polyethylene molecular weight data (M pe ): M pe =A(M ps ) B ; where the value of A is determined iteratively and is approximately 0.42, and the value of B is 1.0. A fifth order polynomial fit is used to fit the corresponding polyethylene equivalent calibration points obtained from equation (1) to their observed elution volumes for each polystyrene standard.
[0031] M N 、M W and M Z Calculated according to the following equation:
[0032]
[0033]
[0034] Among them, Wf i is the weight fraction of the i-th eluted component, and M i is the molecular weight of the i-th eluted component. The molecular weight distribution (MWD) is expressed as M W With M N The ratio of M W / M N The A value is obtained by adjusting the A value in equation (1) until the Mw value and the corresponding retention volume polynomial in equation (3) are consistent with the Mw value with a known M of 120,000. WThe determination was made in agreement with the independently determined value of Mw obtained for a linear homopolymer polyethylene reference of intrinsic viscosity (1.873 dL / g). The same linear homopolymer polyethylene reference was used to determine the response factors of the IR-5 detector, laser light scattering detector, and viscometer. Determination of response factors was performed in a manner consistent with that published in American Chemical Society Publications: "A Strategy for Interpreting Multidetector Size-Exclusion Chromatography Data I" in "Chromatography of Polymers" (ACS Symposium Series, #521), TH Mourey and ST Balke, Chapter 12, page 180, (1993); and "A Strategy for Interpreting Multidetector Size-Exclusion Chromatography Data II" in "Chromatography of Polymers (ACS Symposium Series, #521), ST Balke, R. Thitiratsakul, R. Lew, P. Cheung, TH Mourey, Chapter 13, page 199, (1993), both of which are incorporated herein by reference in their entirety. The IR-5 detector was further calibrated with EPDM resin before electron beam treatment.
[0035] For irradiated terpolymers (i.e., terpolymers exposed to electron beam treatment), candidates for HT GPC analysis were randomly selected and cut into segments. A mixture of segments cut from various terpolymers was used to prepare each HT GPC analyte to overcome any radiation heterogeneity in a single terpolymer sample. HT GPC analytes were prepared at a concentration of approximately 2.0 mg / mL using approximately 60 mg of cut segments and 30 mL of TCB dissolved in a glass bottle with an aluminum foil-lined lid. The analytes were heated at 150°C for 3 hours under gentle agitation and then thermally transferred to an injection vial. The solution in the injection vial was then heated at 160°C for 30 minutes before injection. The injection volume was 200 microliters and the flow rate was 1.0 mL / min. The analyte was filtered through a series filter to remove insoluble material when injected.
[0036] As used herein, the term "initial analyte" is the mass of analyte injected into the HT GPC system. As used herein, the term "filtered analyte" is the mass of analyte that exits the inline filter and is recovered from the IR-5. The weight fraction of the "soluble fraction" is the filtered analyte divided by the initial analyte. For samples containing an insoluble fraction, the reported value is only for the soluble portion of the analyte.
[0037] Four capillary bridge viscometers measure the intrinsic viscosity (η) of the analyte. The g' value of the analyte is calculated as η divided by η 线性 , (i.e., g′=η / η 线性 ), where η 线性 It is the intrinsic viscosity of a linear polymer with the same molecular weight.
[0038] Mass recovery test: Mass recovery (M-REC) was calculated by the expression M-REC = 100 x [(initial analyte - filtered analyte) / initial analyte] using the analyte mass values obtained in the HT GPC test.
[0039] It is understood that polymers having internal crosslinks form insoluble gels which can be quantitatively detected by mass recovery analysis. It is further understood that polymers exhibiting a mass recovery greater than or equal to 85% do not have internal crosslinks.
[0040] The g' value of the irradiated terpolymer is used to calculate the amount of long chain branching. The change in g' value (i.e., the ratio of the g' value of the irradiated terpolymer divided by the g' value of the same non-irradiated terpolymer) is calculated based on the seminal study of long chain branching by Zimm and Stockmeyer, "The Dimensions of Chain Molecules Containing branches and Rings", BH Zimm, WH Stockmayer, The Journal of Chemical Physics, Vol. 17, pp. 1301-1314, 1949, the entire contents of which are incorporated herein by reference. The g values used in the reference are converted to g' values using the following equation, where the empirical value is 0.5:
[0041] g ∈ =g′
[0042] Based on the calculated g' values, the long chain branching per chain was calculated for each resin based on the linear correlation of the number of branches and the g value for tetrafunctional (H-shaped) branched polymers by Zimm and Stockmayer.
[0043] Monomer Content Test: The ethylene and propylene contents of the terpolymers were determined by Fourier Transform Infrared (FTIR) analysis according to ASTM D3900, expressed as weight percent. The ENB content of the terpolymers was determined by Fourier Transform Infrared (FTIR) analysis according to ASTM D6047, expressed as weight percent.
[0044] Residual element analysis test: Residual element analysis was performed using inductively coupled plasma-atomic emission spectrometry (ICP-AES) and X-ray fluorescence (XRF) techniques. For ICP-AES analysis, the sample was weighed into a quartz tube, and 1 mL of water and 3 mL of nitric acid were added to the sample. The sample was placed in a hot block at 115°C for 30 minutes. The sample was then placed in an UltraWave microwave oven, where the sample was digested at 250°C. After microwave digestion, the sample was diluted and analyzed for aluminum, calcium, chromium, titanium, and vanadium by Perkin Elmer ICP. For XRF analysis, the sample was pressed into thin sheets in a hot press at 260°F. The sample was then rinsed with distilled water, and then rinsed with acetone, and the chlorine content was measured by XRF. The results are reported in parts per million (ppm).
[0045] Density is measured according to ASTM D792, Method B. Results are expressed in grams per cubic centimeter (g / cc or g / cm 3 ) as unit report. DETAILED DESCRIPTION
[0046] method
[0047] The present disclosure provides a method. In one embodiment, the method includes providing an ethylene / propylene / non-conjugated polyene terpolymer. The terpolymer is pure and has a Mooney viscosity of less than 100 Mooney units, wherein the Mooney viscosity test condition is ML (1+4) at 125°C. The method includes exposing the pure terpolymer to electron beam radiation. The pure terpolymer is exposed to electron beam radiation at a dose of 0.2 megarads (MRad) to 1.3 MRad. The method includes forming a branched ethylene / propylene / non-conjugated polyene terpolymer. The Mooney viscosity of the branched terpolymer is 25 Mooney units to 135 Mooney units.
[0048] The method includes providing a terpolymer. In an embodiment, the terpolymer is an ethylene / α-olefin / non-conjugated polyene comprising ethylene, α-olefin and non-conjugated polyene in polymerized form. Suitable examples of α-olefins include C3-C20 α-olefins or C3-C8 α-olefins. Suitable examples of non-conjugated polyenes include C4-C40 non-conjugated dienes.
[0049] In one embodiment, the α-olefin is a C3-C8 aliphatic α-olefin. In further embodiments, the α-olefin is selected from the group consisting of propylene, 1-butene, 1-hexene, and 1-octene.
[0050] In one embodiment, the α-olefin is propylene.
[0051] In one embodiment, the non-conjugated polyene is an acyclic diene or a cyclic diene. Non-limiting examples of acyclic dienes include straight chain acyclic dienes, such as 1,4-hexadiene and 1,5-heptadiene; and branched acyclic dienes, such as 5-methyl-1,4-hexadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, 3,7-dimethyl-1,6-octadiene, 3,7-dimethyl-1,7-octadiene, 5,7-dimethyl-1,7-octadiene, and 1,9-decadiene and mixed isomers of dihydromyrcene. Non-limiting examples of cyclic dienes include monocyclic dienes such as 1,4-cyclohexadiene, 1,5-cyclooctadiene, and 1,5-cyclododecadiene; polycyclic alicyclic fused and bridged cyclic dienes such as tetrahydroindene and methyltetrahydroindene; alkenyl, alkylene, cycloalkenyl, and cycloalkylene norbornenes such as 5-methylene-2-norbornene (MNB), 5-ethylidene-2-norbornene (ENB), 5-vinyl-2-norbornene, 5-propenyl-2-norbornene, 5-isopropylidene-2-norbornene, 5-(4-cyclopentenyl)-2-norbornene, and 5-cyclohexylidene-2-norbornene.
[0052] In one embodiment, the non-conjugated polyene has no heteroatoms. As used herein, the term "heteroatom" is an atom other than carbon or hydrogen. The heteroatom can be a non-carbon atom from Groups IV, V, VI, and VII of the periodic table. Non-limiting examples of heteroatoms include: F, N, O, P, B, S, and Si.
[0053] In one embodiment, the non-conjugated polyene is ENB.
[0054] In one embodiment, the terpolymer contains only one type of non-conjugated polyene. The single type of non-conjugated polyene has no, or no, heteroatoms.
[0055] In one embodiment, the terpolymer is an ethylene / propylene / norbornene terpolymer. In another embodiment, the terpolymer is an ethylene / propylene / ENB terpolymer. As used herein, the term "EPDM" is an ethylene / propylene / ENB terpolymer having only three monomers, and ENB is the only diene in the terpolymer.
[0056] In one embodiment, the terpolymer is a pure terpolymer. As used herein, the term "pure" refers to a material that has no oil in or on its structure. As used herein, the term "pure" interchangeably refers to an "oil-free" material. In one embodiment, the EPDM is pure EPDM (i.e., "n-EPDM").
[0057] In one embodiment, the n-EPDM used herein is produced with a metallocene catalyst as described in US Pat. No. 8,101,696, which is incorporated herein by reference in its entirety.
[0058] The Mooney viscosity of n-EPDM is less than 100MU. In one embodiment, the Mooney viscosity of n-EPDM is 20MU, or 30MU, or 40MU, or 50MU, or 60MU, or 65MU, or 70MU to 80MU, or 85MU, or 90MU, or 99MU. In other embodiments, the Mooney viscosity of n-EPDM is 20 to 99MU, or 30 to 99MU, or 60 to 80MU.
[0059] In one embodiment, the Mooney relaxation area (MLRA) of n-EPDM is 25 Mooney unit-seconds (MU·s), or 30 MU·s, or 180 MU·s to 280 MU·s, or 475 MU·s, or 510 MU·s, or 550 MU·s. In other embodiments, the MLRA of n-EPDM is 25 to 550 MU·s, or 30 to 475 MU·s, or 180 to 280 MU·s.
[0060] In one embodiment, the MLRA / ML ratio of n-EPDM is 0.5 seconds (s), or 1s, or 2s, or 3s, or 3.3s to 4s, or 4.5s, or 5s, or 6s, or 6.5s, or 7s, or 7.5s or 8s. In other embodiments, the MLRA / ML ratio of n-EPDM is 0.5 to 8s, or 2 to 6.6s, or 3 to 6s.
[0061] In one embodiment, the n-EPDM has a rheological ratio (RR) of 20, or 25, or 30 or 35 to 40, or 45, or 50, or 55, or 60, or 65. In further embodiments, the n-EPDM has a RR of 20 to 65, or 25 to 60, or 30 to 55.
[0062] The phase angle δ of n-EPDM is greater than or equal to 41°. In one embodiment, the phase angle δ of n-EPDM is 41°, or 45°, or 50° to 60°, or 70° or 85°. In other embodiments, the phase angle δ of n-EPDM is 41° to 85°, or 45° to 70°, or 50° to 60°.
[0063] In one embodiment, the n-EPDM comprises 50 weight percent (wt%), or 55wt%, or 60wt%, or 68wt% to 70wt%, or 72wt%, or 74wt%, or 80wt% polymerized ethylene. In other embodiments, the n-EPDM comprises 50wt% to 80wt%, or 60wt% to 74wt%, or 68wt% to 72wt% polymerized ethylene. In one embodiment, the n-EPDM comprises 23wt%, or 25wt% to 27wt%, or 30wt%, or 35wt%, or 38wt% polymerized propylene. In other embodiments, the n-EPDM comprises 23wt% to 38wt%, or 25wt% to 35wt%, or 25wt% to 30wt% polymerized propylene. In one embodiment, the n-EPDM comprises 0.5 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 3.5 wt%, or 4 wt%, or 4.5 wt%, or 4.7 wt% to 5.1 wt%, or 5.5 wt%, or 6 wt%, or 7 wt%, or 8 wt%, or 8.5 wt%, or 9 wt% polymeric ENB. In further embodiments, the n-EPDM comprises 0.5 wt% to 9 wt%, or 0.5 wt% to 8.5 wt%, or 0.5 wt% to 7 wt%, or 4 wt% to 5 wt% polymeric ENB. The weight percentages are based on the total weight of the n-EPDM.
[0064] In one embodiment, the molecular weight distribution (MWD) of n-EPDM is from 1.8, or 2.0, or 2.2, or 2.4, or 2.6 to 3.1, or 3.2, or 3.5, or 4.0, or 5.0. In other embodiments, the MWD of n-EPDM is from 1.8 to 5.0, or from 2.0 to 4.0, or from 2.2 to 3.5, or from 2.3 to 3.1.
[0065] The n-EPDM may comprise a combination of two or more embodiments as described herein.
[0066] A terpolymer may comprise a combination of two or more embodiments as described herein.
[0067] The method includes exposing a terpolymer (e.g., n-EPDM) to electron beam radiation. In one embodiment, the terpolymer (e.g., n-EPDM) is exposed at a dose of 0.2 megarads (MRad), or 0.3MRad, or 0.4MRad to 0.5MRad, or 0.6MRad, or 0.7MRad, or 0.8MRad, or 0.9MRad, or 1MRad, or 1.1MRad, or 1.2MRad, or 1.3MRad, or 1.5MRad. In other embodiments, the terpolymer (e.g., n-EPDM) is exposed at a dose of 0.2 to 1.3MRad, or 0.3 to 1.2MRad, or 0.3 to 0.9MRad, or 0.3 to 0.7MRad, or 0.4 to 0.5MRad.
[0068] In one embodiment, the terpolymer (e.g., n-EPDM) is exposed to a dose for a time of 1 millisecond (ms), or 2 ms, or 4 ms, or 6 ms, or 8 ms, or 10 ms to 12 ms, or 14 ms, or 18 ms, or 20 ms, or 30 ms, or 100 ms. In other embodiments, the terpolymer (e.g., n-EPDM) is exposed to a dose for a time of 1 to 100 ms, or 2 to 30 ms, or 4 to 20 ms, or 10 to 20 ms.
[0069] In one embodiment, the method utilizes a linear electron beam accelerator. The terpolymer is exposed to electron beam radiation in an ambient air environment. The linear electron beam accelerator is operated under the following conditions: an energy range of 4.5 MeV, a beam power of 150 kW over the entire energy range, a beam energy distribution of + / - 10%, and an average current of 30 milliamps (mA).
[0070] The method includes forming a branched terpolymer (i.e., b-terpolymer). Branched terpolymers are interchangeably referred to as irradiated terpolymers. Branched terpolymers are branched ethylene / alpha-olefin / non-conjugated polyene terpolymers. The alpha-olefin of the branched ethylene / alpha-olefin / non-conjugated polyene terpolymer is any alpha-olefin as described herein. The non-conjugated polyene of the branched ethylene / alpha-olefin / non-conjugated polyene terpolymer is any non-conjugated polyene as described herein. In one embodiment, the branched terpolymer is a branched ethylene / propylene / ENB terpolymer. As used herein, the term "b-EPDM" is a branched ethylene / propylene / ENB terpolymer.
[0071] In one embodiment, the method includes forming a gel-free branched terpolymer. In further embodiments, the method includes forming a gel-free b-EPDM.
[0072] In one embodiment, the Mooney viscosity of the branched terpolymer (e.g., b-EPDM) is 25 MU, or 35 MU, or 45 MU, or 55 MU, or 75 MU, or 95 MU, or 100 MU, or 105 MU, or 110 MU to 115 MU, or 120 MU, or 122 MU, or 125 MU, or 130 MU, or 135 MU. In another embodiment, the Mooney viscosity of the b-EPDM is 25 to 135 MU, or 35 to 120 MU, or 45 to 110 MU. The irradiated terpolymer (e.g., b-EPDM) has an increased Mooney viscosity compared to the non-irradiated terpolymer.
[0073] In one embodiment, the Mooney relaxation area (MLRA) of the branched terpolymer (e.g., b-EPDM) is 220 MU·s, or 280 MU·s, or 315 MU·s to 940 MU·s, or 1800 MU·s, or 2300 MU·s. In other embodiments, the MLRA of b-EPDM is 220 to 2300 MU·s, or 280 to 1800 MU·s, or 315 to 940 MU·s. The irradiated terpolymer (e.g., b-EPDM) has an increased MLRA compared to the non-irradiated terpolymer (e.g., n-EPDM).
[0074] In one embodiment, the MLRA / ML ratio of the branched terpolymer (e.g., b-EPDM) is 7s, or 8s, or 9s, or 10s to 12s, or 13s, or 15s, or 20s, or 24s, or 26s, or 30s. In another embodiment, the MLRA / ML value of b-EPDM is 7 to 30s, or 7 to 26s, or 10 to 15s. Compared with the unirradiated terpolymer, the irradiated terpolymer (e.g., b-EPDM) has an increased MLRA / ML ratio. Without being bound by a particular theory, the MLRA / ML ratio is considered to be the relaxation time associated with the degree of melt elasticity of the terpolymer. Long chain branching (LCB) can slow down the relaxation of the terpolymer and increase the MLRA / ML ratio. The increased MLRA / ML ratio indicates that the irradiated terpolymer contains more LCBs compared to the unirradiated n-EPDM (e.g., n-EPDM).
[0075] In one embodiment, the rheological ratio (RR) of the branched terpolymer (e.g., b-EPDM) is 55, or 60, or 70, or 80, or 90, or 95, or 100 to 105, or 110. In other embodiments, the RR of b-EPDM is 55 to 110, or 60 to 105, or 70 to 100, or 80 to 95. The irradiated terpolymer (e.g., b-EPDM) has an increased RR value compared to the non-irradiated terpolymer. Without being bound by a particular theory, the increased RR value indicates that the irradiated terpolymer has higher shear thinning than the non-irradiated n-EPDM. The increased RR value indicates that the irradiated terpolymer contains more LCBs than the non-irradiated n-EPDM.
[0076] In one embodiment, the phase angle δ of the branched terpolymer (e.g., b-EPDM) is 20°, or 22°, or 25°, or 27°, or 29° to 30°, or 31°, or 32°, or 35°, or 37°, or 39°. In other embodiments, the phase angle δ of b-EPDM is 20° to 39°, or 22° to 37°, or 25° to 35°. Without being bound by a particular theory, it is believed that the irradiated terpolymer (e.g., b-EPDM) has a reduced phase angle δ value compared to the unirradiated n-EPDM. The reduced phase angle δ value indicates that the irradiated terpolymer is more elastic than the unirradiated n-EPDM.
[0077] In one embodiment, the density of the branched terpolymer (e.g., b-EPDM) is greater than or equal to 0.85 g / cc, or 0.86 g / cc to less than or equal to 0.88 g / cc or 0.89 g / cc. In other embodiments, the density of b-EPDM is 0.85 to less than 0.89 g / cc, or 0.86 to 0.88 g / cc.
[0078] In one embodiment, the branched terpolymer (e.g., b-EPDM) comprises vanadium. In one embodiment, the vanadium content of the b-EPDM is greater than or equal to 0 parts per million (ppm), or 0.1 ppm to less than or equal to 0.7 ppm or 0.82 ppm, or 0.9 ppm. In other embodiments, the vanadium content of the b-EPDM is 0 to 0.9 ppm or 0 ppm to less than 0.82 ppm. In one embodiment, the amount of vanadium in the b-EPDM is less than 0.82 ppm.
[0079] In one embodiment, the branched terpolymer (e.g., b-EPDM) contains chlorine. In one embodiment, the chlorine content of the b-EPDM is greater than or equal to 0 parts per million (ppm), or is from 10 ppm to 15 ppm, or is 30 ppm. In other embodiments, the chlorine content of the b-EPDM is from 0 to 30 ppm or from 0 ppm to 15 ppm.
[0080] In one embodiment, the branched terpolymer (e.g., b-EPDM) comprises 54 weight percent (wt%), or 55 wt%, or 60 wt% to 65 wt%, or 68 wt% to 72 wt% polymerized ethylene; 23 wt%, or 25 wt% to 30 wt%, or 40 wt%, or 50 wt%, or 55 wt% polymerized propylene; and 0.3 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 3.5 wt%, or 4 wt%, or 4.5 wt%, or 4.7 wt% to 5.1 wt%, or 5.5 wt%, or 6 wt%, or 7 wt%, or 8 wt%, or 8.6 wt% polymerized ENB. In another embodiment, the b-EPDM comprises 54 wt% to 72 wt%, or 60 wt% to 68 wt% polymerized ethylene; 23 wt% to 55 wt%, or 25 wt% to 50 wt% polymerized propylene; and 0.3 wt% to 8.6 wt%, or 0.5 wt% to 8 wt% polymerized ENB. The weight percentages are based on the total weight of the b-EPDM. Without being bound by a particular theory, it is believed that the reduction in ENB content of the irradiated terpolymer (e.g., b-EPDM) is negligible compared to the non-irradiated n-EPDM. The lack of reduction in ENB content indicates that the irradiated terpolymer is not crosslinked.
[0081] In one embodiment, the branched terpolymer (e.g., b-EPDM) has an MWD of 2.3, or 2.6, or 3.0, or 3.3 to 4.2, or 5.6, or 6. In further embodiments, the b-EPDM has an MWD of 2.3 to 6, or 2.6 to 5.6, or 3.3 to 4.2.
[0082] In one embodiment, the mass recovery of the branched terpolymer (e.g., b-EPDM) is as determined by HTGPC testing. In one embodiment, the mass recovery of b-EPDM is greater than or equal to 80%. In another embodiment, the mass recovery of b-EPDM is 80%, or 85%, or 90% to 95%, or 96%, or 97%, or 98%, or 99%, or 100%. In another embodiment, the mass recovery of b-EPDM is 80% to 100%, or 85% to 100%, or 97% to 100%.
[0083] In one embodiment, the method comprises:
[0084] (1) providing a pure ethylene / propylene / norbornene terpolymer comprising (i) 50 wt% to 80 wt% polymerized ethylene, (ii) 23 wt% to 38 wt% polymerized propylene, and (iii) 0.5 wt% to 9 wt% polymerized ENB, wherein the weight percentages are based on the total weight of the terpolymer;
[0085] (2) exposing a pure ethylene / propylene / norbornene terpolymer to electron beam radiation at a dose of 0.3 to 0.7 MRad; and
[0086] (3) forming a branched ethylene / propylene / norbornene terpolymer having
[0087] (A) a Mooney viscosity of 35 to 120 MU, or 45 to 110 MU, or 55 to 105 MU,
[0088] (B) a rheology ratio at 125°C of 55 to 110, or 60 to 105, or 70 to 100, and
[0089] (C) a phase angle δ of 28° to 39°, or 22° to 37°, or 25° to 35°.
[0090] A method may comprise two or more embodiments disclosed herein.
[0091] Composition
[0092] The present disclosure provides a composition. In one embodiment, the composition comprises a branched ethylene / propylene / non-conjugated polyene terpolymer. The Mooney viscosity (ML 1+4 at 125°C) of the branched terpolymer is 35 Mooney units (MU) to 120MU. The rheological ratio of the branched terpolymer is 55 to 110. The phase angle δ of the branched terpolymer is 20° to 39°.
[0093] In one embodiment, the branched terpolymer is a branched ethylene / propylene / ENB terpolymer (ie, b-EPDM), as previously described herein.
[0094] In one embodiment, the b-EPDM is pure b-EPDM. In other embodiments, the b-EPDM is pure and gel-free b-EPDM.
[0095] In one embodiment, the composition comprises a branched terpolymer (e.g., b-EPDM) in an amount of 5 wt%, or 10 wt%, or 15 wt% to 18 wt%, or 30 wt%, or 50 wt%, based on the total weight of the composition. In another embodiment, the composition comprises a branched terpolymer (e.g., b-EPDM) in an amount of 5 wt% to 50 wt%, or 10 wt% to 30 wt%, or 15 wt% to 18 wt%, based on the total weight of the composition.
[0096] In one embodiment, the composition comprises a pure branched terpolymer (e.g., b-EPDM) having 68 wt% to 72 wt% polymerized ethylene and 4.7 wt% to 5 wt% polymerized ENB, the branched terpolymer having one, some, or all of the following characteristics:
[0097] (i) a Mooney viscosity, ML (1+4) at 125°C, of 36 to 121 MU; and / or
[0098] (ii) a rheological ratio V0.1 / V100 (RR) at 125°C of 62 to 102; and / or
[0099] (iii) a phase angle δ of 31° to 36°; and / or
[0100] (iv) a Mooney relaxation area (MLRA) of 240 to 1795 MU·s; and / or
[0101] (v) MLRA / ML ratio is 7 to 15s.
[0102] In one embodiment, the composition comprises a pure branched terpolymer (e.g., b-EPDM) having 69 wt% to 71 wt% polymerized ethylene and 0.3 wt% to 0.35 wt% polymerized ENB, the branched terpolymer having one, some, or all of the following properties:
[0103] (i) a Mooney viscosity, ML (1+4) at 125°C, of 56 to 63 MU; and / or
[0104] (ii) a rheological ratio V0.1 / V100 (RR) at 125°C of 64 to 87; and / or
[0105] (iii) a phase angle δ of 31° to 37°; and / or
[0106] (iv) a Mooney relaxation area (MLRA) of 348 to 630 MU·s; and / or
[0107] (v) MLRA / ML ratio is 7 to 10s.
[0108] In one embodiment, the composition comprises a pure branched terpolymer (e.g., b-EPDM) having 54 to 55 wt% polymerized ethylene and 8 to 9 wt% polymerized ENB, the branched terpolymer having one, some, or all of the following properties:
[0109] (i) a Mooney viscosity, ML (1+4) at 125°C, of 37 to 103 MU; and / or
[0110] (ii) a rheological ratio V0.1 / V100 (RR) at 125°C of 57 to 107; and / or
[0111] (iii) a phase angle δ of 32° to 38°; and / or
[0112] (iv) a Mooney relaxation area (MLRA) of 315 to 2005 MU·s; and / or
[0113] (v) MLRA / ML ratio is 8 to 20s.
[0114] In one embodiment, the composition has a vanadium content of greater than or equal to 0 parts per million (ppm), or 0.1 ppm to less than or equal to 0.7 ppm, or 0.82 ppm, or 0.9 ppm. In other embodiments, the b-EPDM has a vanadium content of 0 to 0.9 ppm, or 0 ppm to less than 0.82 ppm. In one embodiment, the composition has a vanadium content of less than 0.82 ppm.
[0115] In one embodiment, the composition has a chlorine content greater than or equal to 0 parts per million (ppm), or from 10 ppm to 15 ppm, or 30 ppm. In other embodiments, the b-EPDM has a chlorine content of from 0 to 30 ppm or from 0 ppm to 15 ppm.
[0116] additive
[0117] The compositions of the present invention may optionally contain one or more additives.
[0118] In one embodiment, the composition includes a b-EPDM and an oil. The b-EPDM can be any b-EPDM previously disclosed herein. Oils include, but are not limited to, petroleum oils, such as aromatic and naphthenic oils; polyalkylbenzene oils; organic acid monoesters, such as alkyl and alkoxyalkyl oleates and stearates; organic acid diesters, such as dialkyl, dialkoxyalkyl and alkylaryl phthalates, terephthalates, sebacates, adipates, and glutarates; glycol diesters, such as triethylene glycol dialkanoate, tetraethylene glycol dialkanoate, and polyethylene glycol dialkanoate; trialkyl trimellitates; trialkyl phosphates, trialkoxyalkyl phosphates, alkyl diaryl phosphates, and triaryl phosphates; chloroparaffin oils; coumarone-indene resins; pine tar; vegetable oils, such as castor oil, tall oil, rapeseed oil, and soybean oil, and their ester derivatives and epoxide derivatives; and combinations thereof. In further embodiments, the oil is selected from the group consisting of SUNPAR 2280, PARALUX 6001, HYDROBRITE 550, and CALSOL 5550.
[0119] In one embodiment, the composition comprises an amount of 5wt%, or 15wt%, or 20wt% to 30wt%, or 40wt%, or 70wt% oil, based on the total weight of the composition. In another embodiment, the composition comprises an amount of 5wt% to 70wt%, or 15wt% to 40wt%, 20wt% to 30wt% oil, based on the total weight of the composition.
[0120] An oil may comprise a combination of two or more embodiments as described herein.
[0121] In one embodiment, the composition includes b-EPDM and additives. The b-EPDM can be any b-EPDM previously disclosed herein. Suitable additives include, but are not limited to, fillers, antioxidants and antiozonants, UV stabilizers, flame retardants, colorants or pigments, curing agents (e.g., sulfur, peroxides), accelerators, additives, processing aids, foaming agents, plasticizers, and combinations thereof.
[0122] Fillers include, but are not limited to, carbon black, aluminum silicate, magnesium silicate, calcium silicate, sodium silicate, potassium silicate, and mixtures thereof; calcium carbonate, magnesium carbonate, and mixtures thereof; silicon oxide, calcium oxide, zinc oxide, iron oxide, titanium oxide, and aluminum oxide; calcium sulfate, barium sulfate, and lead sulfate; polyethylene glycol (PEG); sulfur; stearic acid; sulfonamide; alumina trihydrate; magnesium hydroxide; precipitated silica; fumed silica; natural fibers; synthetic fibers; and combinations thereof.
[0123] Antioxidants and antiozonants include, but are not limited to, hindered phenols, bisphenols, and thiobisphenols; and substituted hydroquinones
[0124] In one embodiment, the composition includes b-EPDM and calcium carbonate. In one embodiment, the calcium carbonate is present in an amount of 5wt%, or 15wt%, or 20wt% to 30wt%, or 40wt%, or 70wt%, based on the gross weight of the composition. In other embodiments, the calcium carbonate is present in an amount of 5wt% to 70wt%, or 15wt% to 40wt%, or 20wt% to 30wt%, based on the gross weight of the composition.
[0125] In one embodiment, the composition includes b-EPDM and carbon black. In one embodiment, the carbon black is present in an amount of 5wt%, or 15wt%, or 20wt% to 30wt%, or 40wt%, or 70wt%, based on the total weight of the composition. In other embodiments, the carbon black is present in an amount of 5wt% to 70wt%, or 15wt% to 40wt%, or 20wt% to 30wt%, based on the total weight of the composition.
[0126] In one embodiment, the composition comprises an aggregation additive load, the load excluding calcium carbonate and carbon black. In one embodiment, the aggregation additive load is present in an amount of 0.5wt%, or 1wt%, or 2wt% to 4wt%, or 5wt%, or 10wt%, based on the total weight of the composition. In other embodiments, the aggregation additive load is present in an amount of 0.5wt% to 10wt%, or 1wt% to 5wt%, or 2wt% to 4wt%, based on the total weight of the composition.
[0127] An additive may comprise two or more embodiments disclosed herein.
[0128] An aggregation additive loading may comprise two or more embodiments disclosed herein.
[0129] In one embodiment, the composition comprises a branched terpolymer (e.g., b-EPDM) in an amount of 5 wt%, or 10 wt%, or 15 wt% to 18 wt%, or 30 wt%, or 50 wt%, based on the total weight of the composition. In another embodiment, the composition comprises a branched terpolymer (e.g., b-EPDM) in an amount of 5 wt% to 50 wt%, or 10 wt% to 30 wt%, or 15 wt% to 18 wt%, based on the total weight of the composition.
[0130] A composition may comprise two or more embodiments disclosed herein.
[0131] The composition can be used to form an article. Non-limiting examples of articles that can be formed from the composition include belts, cables, extrusion profiles, hoses, moldings, roofing membranes, sponges, tires, weather stripping, and wire.
[0132] The present disclosure is more fully described by the following examples. Unless otherwise indicated, all parts and percentages are by weight.
[0133] Examples
[0134] The raw materials used to formulate the comparative samples ("CS") and the inventive examples ("IE") are provided in Table 1 below.
[0135] Table 1
[0136]
[0137] Comparative samples CS1, CS4, CS9, CS12, CS15, CS18 and CS19 are pure EPDM on a non-irradiated basis used as received. Comparative samples CS7 and CS8 are ZN-catalyzed pure EPDM used as received. See Table 2.
[0138] Branched EPDM (b-EPDM) was produced by irradiating pure EPDM with a dose time of 10 to 20 milliseconds (ms) in air using a DYNAMITRON linear electron beam accelerator (Table 2). The operating parameters of the electron beam accelerator were: energy range of 4.5 MeV, beam power of 150 kW over the entire energy range, beam energy distribution of + / -10%, and an average current of 30 milliamperes (mA).
[0139] Comparative samples CS2 and CS3 were produced by irradiating CS 1. Comparative samples CS6, CS11, CS14, and CS17 were produced by irradiating CS4, CS9, CS12, and CS15, respectively.
[0140] Inventive Examples IE1 and IE2 were produced by irradiation CS1. Inventive Examples IE3 and IE4 were produced by irradiation CS4. Inventive Examples IE5 and IE6 were produced by irradiation CS9 and CS12, respectively. Inventive Examples IE7 and IE8 were produced by irradiation CS15. Inventive Examples IE9 and IE10 were produced by irradiation CS18. Inventive Examples IE11 and IE12 were produced by irradiation CS19.
[0141] Table 2 summarizes the results of irradiation for a range of properties of comparative samples and inventive examples. Table 2 includes the vanadium content (V) and chlorine content (Cl) from residual elemental analysis testing. The abbreviation NM indicates that a property of the index sample was not measured.
[0142] Table 2
[0143]
[0144]
[0145] Table 2 shows that b-EPDM has increased MV values compared to base EPDM. For NORDEL4760, NORDEL4770, NORDEL 4785, and NORDEL 6565, the MV increased from 59.5MU to 81.1MU (IE4), from 69.4MU to 107.4MU (IE5), from 83.8MU to 120.4MU (IE6), and from 66MU to 103MU (IE12), respectively, after irradiation at a dose of 0.7MRad. The MV values of CS6 (163.1), CS11 (162.2MU), and CS14 (165.1MU) were accompanied by evidence of macrogel formation, indicating that b-EPDM has undesirable crosslinking after irradiation at a dose of 1.5MRad.
[0146] Applicants unexpectedly found that irradiating NORDEL 4770 (IE5) at a dose of 0.7 MRad, MV shifted from 69.4 MU to 107.4, RR shifted from 42.5 to 102.2, and phase angle δ shifted from 48 to 31. Irradiating NORDEL 4785 (IE6) at a dose of 0.7 MRad, MV shifted from 83.8 MU to 120.4, RR shifted from 43.7 to 99.8, and δ shifted from 50 to 33.
[0147] Table 2 summarizes the results of the electron beam irradiation on the molecular weight distribution (MWD) and mass recovery (M-REC) values. Applicants unexpectedly discovered that irradiating NORDEL 4725 (IE1), NORDEL 4785 (IE6) and NORDEL 3745 (IE7) at a dose of 0.7 MRad produced b-EPDM with a mass recovery of 100%. The mass recovery of 100% indicates the presence of chain branching in the absence of crosslinking in the b-EPDM.
[0148] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments occurring within the scope of the appended claims.
Claims
1. A method for controlling long chain branching, comprising: Providing a pure ethylene / propylene / non-conjugated polyene terpolymer (n-terpolymer) having a Mooney viscosity ML (1+4) at 125° C. of less than 100 Mooney units (MU); exposing the n-terpolymer to electron beam radiation at a dose of 0.2 megarads (MRad) to 1.3 MRad; and A branched ethylene / propylene / non-conjugated polyene terpolymer (b-terpolymer) having a Mooney viscosity ML (1+4) at 125° C. of 25 MU to 135 MU is formed.
2. The method according to claim 1, wherein the rheological ratio of the n-terpolymer is 20 to 65, the method comprising b-terpolymers having rheological ratios of 55 to 110 were formed.
3. The method according to any one of claims 1 to 2, wherein the phase angle δ of the n-terpolymer is greater than or equal to 41°, the method comprising b-terpolymers are formed having a phase angle δ of 20° to 39°.
4. The method of claim 1 or 2, comprising forming the b-terpolymer with a mass recovery greater than or equal to 85%.
5. The method according to claim 1 or 2, comprising: providing an n-terpolymer comprising 0.5 wt % to 9.0 wt % norbornene; and A b-terpolymer containing 0.3 to 8.6 wt % norbornene is formed.
6. The method according to claim 1 or 2, comprising: Provided is a pure ethylene / propylene / norbornene terpolymer (n-EPDM) comprising (i) 50 wt% to 80 wt% ethylene, (ii) 23 wt% to 38 wt% propylene, and (iii) 0.5 wt % to 9.0 wt % norbornene; exposing the n-EPDM to electron beam radiation at a dose of 0.3 MRad to 0.7 MRad; and A branched ethylene / propylene / norbornene terpolymer (b-EPDM) was formed having the following (A) Mooney viscosity ML (1+4) at 125°C of 35 MU to 120 MU, (B) a rheological ratio of 55 to 110, and (C) Phase angle δ of 25° to 39°.
7. The method of claim 1 or 2, comprising providing an n-EPDM, wherein the n-EPDM comprises only one type of non-conjugated polyene, and the non-conjugated polyene has no heteroatoms.
8. A composition comprising: A branched pure ethylene / propylene / non-conjugated polyene terpolymer (b-terpolymer) formed by the process according to any one of claims 1 to 7, wherein the branched pure ethylene / propylene / non-conjugated polyene terpolymer comprises (A) Mooney viscosity ML 1+4 at 125°C of 35 MU to 120 MU; (B) a rheological ratio of 55 to 110; and (C) Phase angle δ ranging from 20° to 39°.
9. The composition of claim 8, wherein the mass recovery of the b-terpolymer is greater than or equal to 80%.
10. The composition of claim 8, wherein the b-terpolymer comprises less than or equal to 0.82 parts per million (ppm) vanadium when measured by inductively coupled plasma-atomic emission spectroscopy (ICP-AES).
11. The composition of claim 8, wherein the b-terpolymer comprises (i) 54 to 72 weight percent ethylene; (ii) 23 wt% to 55 wt% propylene; and (iii) 0.3 wt% to 8.6 wt% norbornene.
12. The composition of claim 8, wherein the b-terpolymer has a density greater than or equal to 0.85 g / cc and less than 0.89 g / cc.
13. The composition of claim 8, wherein the b-terpolymer has a chlorine content of greater than or equal to 0 parts per million (ppm) to less than or equal to 30 parts per million (ppm).
14. The composition of claim 8, wherein the b-terpolymer comprises n-EPDM, wherein the n-EPDM comprises only one type of non-conjugated polyene, and the non-conjugated polyene has no heteroatoms.
Citation Information
Patent Citations
Polyolefin solution polymerization process and polymer
US8101696B2
Ethylene copolymer with in-situ oil production
CN107922689A